2019
DOI: 10.14309/ajg.0000000000000460
|View full text |Cite
|
Sign up to set email alerts
|

Long-Duration Oral Vancomycin to Treat Clostridioides difficile in Patients With Inflammatory Bowel Disease Is Associated With a Low Rate of Recurrence

Abstract: OBJECTIVES: Patients with inflammatory bowel disease (IBD) are susceptible to Clostridioides difficile infections (CDIs), suffering from greater morbidity and mortality than the general population. Previous studies have proven the efficacy of oral vancomycin therapy in CDI, but there are no definitive guidelines to treat patients with IBD. We assessed the relationship between the length of vancomycin therapy and rates of CDI recurrence and reinfection in patients with IBD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…This study further confirms the ability of intestinal microflora to modulate the gastrointestinal dopaminergic system [ 44 ]. Although vancomycin has been an important medication in the treatment of IBD flares associated with Clostridium difficile , as well as dysbiosis, and should also be considered a frontline antibiotic therapy in IBD [ 64 ], its use might be associated with alterations in the gastrointestinal catecholamine turnover and the expansion of colitogenic bacteria (Mucispirillum, Desulfovibrio, and Helicobacteraceae) [ 44 ]. Yet, no comparison was made between TRUC mice treated with antibiotics versus wild-type mice.…”
Section: Resultsmentioning
confidence: 99%
“…This study further confirms the ability of intestinal microflora to modulate the gastrointestinal dopaminergic system [ 44 ]. Although vancomycin has been an important medication in the treatment of IBD flares associated with Clostridium difficile , as well as dysbiosis, and should also be considered a frontline antibiotic therapy in IBD [ 64 ], its use might be associated with alterations in the gastrointestinal catecholamine turnover and the expansion of colitogenic bacteria (Mucispirillum, Desulfovibrio, and Helicobacteraceae) [ 44 ]. Yet, no comparison was made between TRUC mice treated with antibiotics versus wild-type mice.…”
Section: Resultsmentioning
confidence: 99%
“…In another retrospective study comparing, rates of CDI recurrence and reinfection in IBD patients receiving long (21-42 days) or shortduration (10-14 days) oral vancomycin therapy, demonstrated a 1.8% incidence of CDI recurrence in the long-duration compared to 11.7% in the short-duration treatment group. 49 A retrospective study evaluated fidaxomicin use in 21 IBD patients who had CDI and demonstrated that all patients responded either with symptom improvement or a negative C. difficile test. The rate of recurrent CDI was 19% with a median time to recurrence of 29 days.…”
Section: Vancomycin or Fidaxomicin But Not Metronidazolementioning
confidence: 99%
“…Antibiotic therapy should be reserved for patients with documented infections such as intra-abdominal abscesses or C. difficile. In patients with C. difficile infection in particular, oral vancomycin is considered firstline therapy for 10-14 days, though prolonged duration of therapy may prevent recurrence rates within 8 weeks of antibiotic discontinuation [24,48].…”
Section: Management Of Hospitalized Inflammatory Crohn's Diseasementioning
confidence: 99%